Prof. K.H. Zainal Abidin Fikri dan Peran Intelektual, Sosial Keagamaan di Palembang, Sumatera Selatan (1334-1411 H / 1916-1990 M) - Jemi Posa; Nor Huda; Otoman Otoman (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2022)
This study explains the role of Prof. K. H. Zainal Abidin Fikri from his intellectual and socio-religious knowledge in the field of da’wah and Islamic education in the city of Palembang. This study uses qualitative data types. This study is focused on answering the main problems, among other: First, how is the intellectual biography of Prof. K. H. Zainal Abidin fikri. Second, what is the role of Prof. K. H. Zainal Abidin fikri in the field of religious social and Islamic education in Palembang. This study uses role theory and uses a historical research methodology with four stages: heuristics, source criticism, interpretation, and historiography. The data sources used are first, interviews conducted with zuriat and her students, her work is entitled Al-Lisanuzzikri. Meanwhile, secondary data are books, journals, and arcticles, related to this research. The results of this study are Prof. K. H. Zainal Abidin Fikri played a role in developing Islam in Palembang. In the socio-religious field, he was active in lectures in almost all mosques in the city of Palembang and its surroundings, his thoughts ware also poured out, such as straightening the words of consent at that time. Counseling with kyai or religious leaders is also encouraged. In the education of Prof. K. H. Zainal Abidin Fikri plays a role in providing teaching in formal and non-formal education both at the IAIN Raden Fatah Palembang college as well as at the Masjid Agung and his own house both about religious sciences to Thoriqoh Naqsyabandiyah Al-Mujaddadiyah.